Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evalu ation, this briefer book provides an overall framework and essential c hecklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utiliza tion-focused evaluation process as a complex adaptive system, incorpor ating current understandings about systems thinking and complexity con cepts. The book integrates theory and practice, is based on both resea rch and professional experience, and offers new case examples and cart oons with Patton's signature humor.
Keywords: Reference / Research; Research